Effects of touch target location on performance and physical demands of computer touchscreen use. - Kang, Hwayeong; Shin, Gwanseob (Applied Ergonomics, 2017)
Touchscreen interfaces for computers are known to cause greater physical stress compared to traditional computer interfaces. The objective of this study was to evaluate how physical demands and task performance of a tap gesture on a computer touchscreen vary between target locations and display positions. Twenty-three healthy participants conducted reach-tap-return trials with touch targets at fifteen locations in three display positions. Mean completion time, touch accuracy and electromyography of the shoulder and neck extensor muscles were compared between the target locations and display positions. The results demonstrated that participants completed the trial 12%-27% faster with 13%-39% less muscle activity when interacting with targets in the lower area of the display compared to when tapping upper targets (p < 0.05). The findings suggest that proper target placement and display positioning can improve task performance and lessen physical demands of computer touchscreen interface use.